Recontextualizing Situational Crisis Communication Theory for Ethnicity, Religion, Race, and Intergroup Relations-Sensitive Crisis Communication in Indonesia through the Case of "Muhammad-Maria" - Mikyal Azzahra, Ghevira; Don Bosco Doho, Yohannes (Journal of English Language and Education, 2026)
This study recontextualizes Situational Crisis Communication Theory (SCCT) to better explain crises involving ethnicity, religion, race, and intergroup relations (SARA) in Indonesia through the case of Holywings’ “Muhammad–Maria” promotion in 2022. Using a qualitative design that combines an integrative literature review and an intrinsic case study, the research develops the Culturalized SCCT Model for SARA-Based Crises (CSM–SARA). Empirical data were collected through desk research from multiple sources, including mainstream media reports (such as CNN Indonesia, Detik, Kompas, and Suara.com), official statements from Holywings, government and police announcements, legal documents related to regulatory actions, and Holywings’ social media posts. The data were analyzed using template analysis based on six categories in the proposed model. The findings show that SARA-related crises extend beyond reputational threats and begin with sacred-value violations that trigger moral outrage, strong attributions of responsibility, and government intervention. These dynamics highlight the importance of culturally grounded crisis responses and the restoration of social legitimacy. The CSM–SARA model extends SCCT by providing a framework better suited to religiously and culturally plural societies such as Indonesia.